Entrepreneurship in Aseer Region: Challenges and Solutions - Alshahrani, Rawabi; Alsufran, Mohammed (The Arab Journal of Administration, 2025)
The study aimed to analyze the challenges facing entrepreneurship in the Aseer region, focusing on business incubators and entrepreneurs, using a qualitative approach for data collection and analysis. The findings revealed a set of significant challenges confronting business incubators. These include a lack of qualified personnel capable of effectively managing and supporting entrepreneurial projects, a weak entrepreneurial culture that limits innovation and creativity, ineffective coordination with government entities, and financial obstacles that hinder the achievement of desired goals and long-term sustainability. ‏In addition, the study identified major barriers faced by entrepreneurs. These challenges encompass marketing difficulties due to limited access to modern tools and platforms, financial constraints resulting from insufficient funding opportunities, and a lack of practical experience necessary to manage and scale their businesses effectively. Entrepreneurs also face recurring operational problems, social challenges that affect their network and community support, and high real estate costs, which further limit their ability to develop and sustain their projects. ‏Based on these findings, the study recommended encouraging the establishment and development of business incubators in the Aseer region by providing the necessary financial, administrative, and technical support. Furthermore, it called for fostering collaborations with local companies to enhance entrepreneurs’ marketing and management skills through tailored education and training programs. Strengthening partnerships between specialized companies to exchange knowledge and expertise is essential for improving the entrepreneurial environment and achieving sustainable economic development